Appearance performance of commercial hijab fabrics / Nur Ain Yusof and Nor Juliana Mohd Yusof - Yusof, Nur Ain; Mohd Yusof, Nor Juliana (UiTM Press and Research Management Centre Universiti Teknologi MARA, 2020)
Muslim women are required to wear hijab as a religious obligation which symbolizes women’s faith to the creator (Quran 24:21). Many types of hijab are available in the market, with ready-to-wear (RTW) hijab being the most popular choice of hijab in Malaysia. Limited knowledge of fabric characteristics among consumers has created dissatisfaction in many aspects of hijab performance associated with appearance and comfort. This paper presented the study of hijab appearance performances. Ten commercial fabrics (cotton, tetron cotton, silk, rayon, crepe back satin, Valentino dull satin, chiffon crepe, French voile, and koshibo) which are commonly used in hijab making, were investigated. Stiffness, drape, wrinkle aspect, pilling, and snagging of fabric, which is associated with hijab appearance, were examined. A fabric ranking index was then developed to support the analysis further. In order to validate the result, a wear test was conducted where the tested fabrics were developed into hijabs and wear assessment was conducted. Feedback from the respondents was obtained and compared with the fabric ranking index. The results of this study concluded that koshibo, Valentino dull satin, chiffon crepe and French voile exhibited the highest performance ranking among all the fabric tested. The study provides the reference to hijab manufacturers and end-users in selecting the most suitable fabric for hijab in terms of the respective appearance properties.